2015
DOI: 10.1016/j.rbmo.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Mmu-miR-126a-3p plays a role in murine embryo implantation by regulating Itga11

Abstract: miR-126a-3p has been found to be specifically up-regulated in the process of murine embryo implantation. This study aimed to further clarify the role of miR-126a-3p in embryo implantation. The expression of miR-126a-3p in implantation sites was significantly higher than that in interimplantation sites (P = 0.009). Its expression dynamics in a series of models, including pseudopregnancy, delayed implantation and artificial decidualization, suggested that the induction of miR-126a-3p is dependent on hormonal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Based on the present ceRNA networks results and gene ontology analysis in the GSE137445 array dataset, three miRNAs (miR-486, miR-516b-5p and miR-584-3p) binding to both FEZF1-AS1 and ITGA11 were identified. Furthermore, three other miRNAs (miR-126a, miR-29b and miR-145) targeting ITGA11 were selected based on previous reports (29)(30)(31). After miRNA overexpression, miR-516b-5p significantly downregulated FEZF1-AS1 expression ( Fig.…”
Section: Fezf1-as1 Can Compete With Mir-516b-5p For Direct Binding Tomentioning
confidence: 99%
“…Based on the present ceRNA networks results and gene ontology analysis in the GSE137445 array dataset, three miRNAs (miR-486, miR-516b-5p and miR-584-3p) binding to both FEZF1-AS1 and ITGA11 were identified. Furthermore, three other miRNAs (miR-126a, miR-29b and miR-145) targeting ITGA11 were selected based on previous reports (29)(30)(31). After miRNA overexpression, miR-516b-5p significantly downregulated FEZF1-AS1 expression ( Fig.…”
Section: Fezf1-as1 Can Compete With Mir-516b-5p For Direct Binding Tomentioning
confidence: 99%
“…Enhancement of miR-429 resulted in suppression of the migratory and invasive capacities of cells, probably through targeting protocadherin 8, leading to reduced implantation sites [ 28 ]. On the contrary, miR-126-3p was specifically up-regulated in implantation sites, promoting cell migratory and invasive capacity by regulating the expression of integrin α11 [ 29 ]. Moreover, we know that sex hormones induce changes in miRNA expression in the endometrium, for example, progesterone induced the expression of miR-125b in human endometrial epithelium cells.…”
Section: Ncrnas and Embryo Implantationmentioning
confidence: 99%
“…13 These regulatory RNAs are involved in diverse biological processes, and their aberrant expression is associated with various pathological processes and diseases, such as cancer and diabetes. 14 Additionally, miRNAs have been reported to play important roles in cellular proliferation, differentiation, and apoptosis as well as the implantation process. 1 Notably, a number of studies have shown that miRNAs can specifically affect infertility and the human reproductive system, 15 and it has recently been reported that miRNAs can regulate RIF occurrence.…”
Section: Introductionmentioning
confidence: 99%